A detail shape grammar. Using Alberti's column system rules to evaluate the longitudinal elevation of the nave of Sant'Andrea church generation. Issue 3 (3rd April 2018) - D'Oliveira Quaresma, Pedro Filipe Coutinho Cabral
Abstract: This paper shows the way Leon Battista Alberti treatise De Re Aedificatoria column systematization shape grammar was built, and how the longitudinal elevation of the nave of the Sant'Andrea church was designed, evidencing some steps involved in the grammar construction process, its derivation, and the partial outputs gained from the grammar evaluation. The goal of this grammar is to infer Alberti's treatise rules through a computational approach evidencing its algorithmic nature, illustrating it, and understanding the De Re Aedificatoria rules that may be applied in the generation of some parts of buildings such as the Sant'Andrea church, showing a complementary method to archaeological, bibliographical, historical ones, among others, that have been used to understand the built environment. The rules provided by the grammar may be applied to an initial insertion point to produce a complete column and to a pre-existing plan or section element of a building generating its facade. It was proved, evaluating the grammar with a simple linear regression method, to what extent the treatise influenced the design of the facade in the study.